(untitled) (International Journal of Nursing Education, 2021)
Background & Objectives: The study aim to assess the effect of phototherapy with aluminum foil reflector on level of bilirubin among neonates with hyperbilirubinemia in selected hospital in Panipat, Haryana. Materials & Methods: The methodology of the present study was a Qusi-experimental research design. Sample size of the study was 60 (i.e. 30 each for experimental and control group) neonates selected with convenient sampling technique. Standardized tool (i.e. Kramer scale) with baseline characteristics was used for data collection. Data analysis was done to with the help of descriptive and inferential statistics. Results: The study findings reveal with regard to mean of baseline characteristics in experimental group the mean ± S.D. of pretest value is 12.97 ±1.732. But in post test the mean ±S.D. value is 17.30 &1.119. The Df value is 29 and t value is 12.868 and the result is significant. In control group the mean ±S.D. of pre-test value is 12.300 & 1.418.but in posttest the mean ±S.D. value is 16.43 & 1.654. The Df value is 29 and t value is 14.628 and result is significant. In Kramer scale of experimental group the mean ±S.D. of pretest value is 8.83 & 2.086. But in post test the mean ±S.D. value is 1.87 & 1.306. The Df value is 29 and t value is 18.094 and the result is significant. In control group the mean ±S.D. of pre-test value is 7.867 & 2.030. But in posttest the mean ±S.D. value is 1.10 & 0.548. The Df value is 29 and t value is 16.907 and result is significant. Hence, phototherapy with aluminum foil reflector was effective on level of bilirubin among neonates there was statically significant association between pre-test and post test level of knowledge of sample with socio-demographic variables like gender etc. Conclusion: The study concluded that the phototherapy with aluminum foil reflector was effective on level of bilirubin among neonates.